ANALISA PENGARUH KELENJAR HYPOFISA KODOK PURU ( Bufo Melanustickus ) TERHADAP KELANGSUNGAN HIDUP LARVA DUMBO ( Clarias gariepinus ) - Irianty Tampubolon; Frits A. Maitindom; Yonavin M. Titaley; Margret I. Solissa; Satria Mandiangan; Marry H. Lidan (Nusantara Hasana Journal, 2026)
This study aims to determine the survival rate of African catfish larvae due to the administration of pituitary gland doses of puru toad with different doses. The container used was a jar measuring 30 × 20 × 20 cm as many as 9 jars according to the number of experimental units. The water height is ± 15 cm, with a water volume of 4.1. The broodstock of catfish used were 9 females weighing 1 kg each. Puru toad used as many as 133 tails. The experimental design used was a Completely Randomized Design (CRD) with 3 treatments and 3 replications, with different levels of pituitary gland doses of each treatment A = 600 mg / kg African catfish, treatment B 700 mg / kg African and treatment C = 800 mg / kg African catfish. Calculation of egg hatchability was carried out after 18-24 hours. While the calculation of larval survival after 3 days of larval maintenance. The analysis of variance showed that the pituitary gland treatment did not significantly affect the survival of African catfish larvae. The highest survival rate was found in the 600 mg/kg African catfish treatment, at 8.21%. This was followed by the 800 mg/kg African catfish treatment, at 5.46%, and the 700 mg/kg African catfish treatment, at 4.61%. Temperature and pH remained normal throughout the study.